Impact of Boron Toxicity and Humic Substance Applications on Cotton Fiber Quality and Yield - Mustafa Ali Kaptan; Mehmet Aydın (Turkish Journal of Agriculture: Food Science and Technology)
This study investigated the effects of boron toxicity and humic substance applications on cotton fiber quality and yield over two consecutive years, targeting boron toxicity issues in soils affected by agricultural and geothermal activities. The experiment evaluated varying concentrations of boron (0.6–1.8–5.4–16.2 mg B l-1) and humic substances (0–200–400 kg ha-1), with a focus on their effects on seed cotton yield, fiber length, fineness, strength, and gin efficiency. In the first year, the highest seed cotton yield was recorded at 452.5 kg da-1 with the B1 application, followed by 428.3 kg da-1 with B2. In the second year, increased boron application led to a notable decrease in seed cotton yield, with the lowest yield at 99.3 kg da-1 for the B4 application. The highest dose of boron also significantly reduced fiber strength, with the lowest recorded at 31.57 g/tex, and gin efficiency, which dropped to 37.98%. Humic substance applications showed limited influence on fiber quality parameters; however, the highest dose (H3) led to a significant increase in fiber strength to 33.47 g/tex in the second year. Cotton leaves accumulated substantial amounts of boron, reaching concentrations of 2048 mg B kg-1 during the flowering period of the second year, suggesting that cotton could serve as a hyperaccumulator in phytoremediation efforts for boron-contaminated soils. The study further determined that cotton can tolerate boron concentrations in irrigation water ranging from 1.8 to 5.4 mg B l-1, making it a viable crop in boron-affected regions. These findings provide critical insights into the potential of cotton as a resilient crop in environments with elevated boron levels, underscoring the need for further research to optimize cotton cultivation under such conditions.